Narrative review of soundscape studies - Chieng, Julia; Chan, Cheong Jan (Human Resource Management Academic Research Society, 2021)
Soundscape generally refers to the sonic environment. The study of soundscape is significant to improve the quality of the environment, enhance the function of a place and promote a healthy and quality life as well as for the understanding of cultures. Given approximately half a century of scholarly studies on soundscape, the purpose of this conceptual paper is to present a narrative review of the literature on its definitions, methods, fields and space types from various disciplines to provide an overview and reference to novice soundscape researchers. As it is a wide-ranging field, soundscape study inherently encompasses research from multiple disciplines and mostly necessitates cross-disciplinary approaches. Among the diversity with different emphases on research frameworks and methodologies, soundscape research usually incorporates the three elements of acoustic properties, perception and place. The study can be for documentation, description, management and/or creation of soundscape. Some of the fields of soundscape study involve acoustic ecology, acoustemology, ecomusicology, acoustic engineering, artistic creativity or wellbeing. Data were usually collected through audio recordings, measurements of sound levels, soundwalks, questionnaires and interviews. Soundscape research has been increasing in America and European countries and can potentially be further expanded on different distinctive sound environments, ecosystems and sociocultural lifestyles.